Need Analysis in English Learning Media for Buddhist Students of Kusalamitra Homeschooling - Arina Afiyati Shadikah (The New Perspective in Theology and Religious Studies, 2023)
This study aimed to analyze the need of Buddhist students in learning English. It was used to determine the most suitable English learning media for them. The recent study was done at Kusalamitra homeschooling at the level of Senior High School students. This study belonged to qualitative research with case study approach. There were 30 students involved in this study. Questionnaires and interview were used to collect the data in this research. The data gathered then analyzed qualitatively with three steps, namely data collection, data reduction and data verification or can be called drawing conclusion. Based on the data analyzed, there was a research finding. The students need a handy supplementary material which could be used and carried easily. Thus the researcher needed to develop an Information and Communication Technology that contained supplementary material for learning English.